An Original Approach to Evaluating the Quality of Blood Donor Selection: Checking Donor Questionnaires and Analyzing Donor Deferral Rate - Gillet, Philippe; Neijens, Esther (Frontiers in Medicine, 2018)
Blood donor selection is a cornerstone for blood transfusion safety, designed to safeguard the health of both donors and recipients. In the Service Francophone du Sang (SFS), health professionals (HPs) are allowed to interview donors on their own after formal qualification. This qualification is afterwards evaluated by means of two complementary quality indicators: monitoring of donor health questionnaires (DHQs) and analysis of donor deferral rate. The study aims to evaluate the degree to which both quality indicators may be useful and appropriate tools to evaluate the quality of blood donor selection. An analysis performed on 2016 data showed that noncompliance detected by means of DHQ monitoring seems to be more frequent in HPs who conduct a low number of interviews compared to all HPs as a group (5.67% vs. 3.23%; p<0.001). Deferral rates are also higher in HPs with a lower activity compared to HPs who interview more donors (14.80% vs. 13.00%, p<0.001). Furthermore, statistically differences are observed between the type of blood donation venue in terms of the global deferral rate (for instance fixed site vs. schools: 11.9% vs. 19.5%; p<0.001), and specific reasons for deferral (such as sexual risk behavior and travel in at-risk areas, the differences being highly significant between each category of blood donation venue; p<0.001). Providing the HPs with feedback on these findings was an opportunity to draw their attention to some aspects of the selection process in order to improve it.